Effects of increasing dietary bakery by-product on growing-finishing pig growth performance and carcass quality - Paulk, C.B.; Nitikanchana, S.; Prusa, K.J.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
A total of 1,263 pigs (PIC 337 × 1050; initially 77.8 lb) were used in a 102-d study to determine the effects of dietary bakery by-product on pig growth performance and carcass quality. Pigs were randomly assigned to pens based on gender (14 barrow pens, 11 gilt pens, and 23 mixed-gender pens). Pens of pigs were allotted to 1 of 3 dietary treatments in a completely randomized design while balancing for initial BW and gender. Dietary treatments included 0, 7.5, and 15% bakery by-product. On d 84, the 5 heaviest pigs from each pen (determined visually) were sold according to the normal marketing procedure of the farm. On d 102, the remaining pigs were individually tattooed by pen number and sent to harvest to allow for collection of carcass data. On d 84 and d 102, the median weight market pig from every pen was selected (determined visually) for collection of carcass quality measurements.
Keywords: Swine; bakery by-product,; Carcass quality; Finishing pig